„Nagy idő múlt a nagy harc óta!”: A kőszívű ember fiai emlékezeti munkája - Bényei, Péter (Studia Litteraria, 2018)
Mór Jókai’s novel, A kőszívű ember fiai (The Baron’s Sons), published in 1869, has become one of the cornerstones of national memory regarding the 1848-49 Hungarian Revolution and War of Independence in the 20th century, and in the past century in academic writing it has been interwoven with the notions of mythical novel and new national origin story. However, the result of the closer rereading of the novel led to the conclusion that The Baron’s Sons may not have become one of the outstanding bearers of the 48-49 memory because of its layered representation of the past and its memory work that easily leaps through time, but the lengthy embedding work of the Hungarian collective memory might have been needed (as well). The Baron’s Sons can be best described by its genre-poetical forms, it was fundamentally a popular novel, deeply rooted in the present of its time of creation, it satisfied the contemporary reader in many ways (adventure fiction, fitted for serialization etc.). While it considers the heroic and tragic fights of the (near) past, it offers points for orientation to understand its age, and it uses appropriate acting strategies fit for outlining the values of the reshaping society. To describe these notions Biedermeier’s conceptual net offers some grasping points: the staging of the moving on after the end of the mourning, the deheroisation and the placing of the events in the distancing memory all serve the revelation of safety, homeliness, and conservation in the novel.